Faktor Penghambat Peran Intelijen Kejaksaan Negeri Kabupaten Wajo Dalam Pengungkapan Dugaan Tindak Pidana Korupsi - Ali, Ismail; Mustafa, Dewi Wahyuni; Magfirah, Nurul; Lestari, Wina Dina; Azzahra, Fatimah; Amran, Andi Salsabila; Ryan, Muhammad (YP-SDI Lamaddukelleng, 2024)
Exploring the inhibiting factors in the intelligence role of the Wajo District Attorney's Office is the purpose of this research. In general, the literature method and the method of direct interviews and field observations for in-depth exploration of data and information. Then, the resulting data will be analyzed using qualitative descriptive methods. This study found that the inhibiting factors of Wajo District Attorney's intelligence in carrying out its role are the existence of organizations or individuals related to cases that are not cooperative in providing information, poor governance systems, ineffective work methods, and problems and obstacles faced by witnesses in providing information or information required by investigators.